Wavelength-Tunable Chirped Pulse Amplification System (1720 nm–1800 nm) Based on Thulium-Doped Fiber - Xinyang Liu; Regina Gumenyuk (Photonics, 2024)
Chirped pulse amplification (CPA) has been a commonly used methodology to obtain powerful ultrashort laser pulses ever since its first demonstration. However, wavelength-tunable CPA systems are much less common. Wavelength-tunable ultrashort and intense laser pulses are desirable in various fields such as nonlinear spectroscopy and optical parametric amplification. In this work, we report a 1720 nm–1800 nm tunable CPA system based on Tm-doped fiber. The tunable CPA system contains a seed laser, a pulse stretcher, two cascaded amplifiers and a pulse compressor. The dispersion-managed seed laser cavity emits wavelength-tunable laser pulses with pulse durations of several ps and spectral widths from 25 nm to 34 nm. After being stretched temporally to tens of ps, the laser pulses are then amplified in two-stage amplifiers and compressed in a Treacy-type compressor. At 1720 nm, the maximum average power of 126 mW is obtained with a pulse duration of 507 fs; at 1800 nm, the maximum average power of 264 mW is obtained with a pulse duration of 294 fs. The pulse repetition rates are around 22.7 MHz. We perform an analysis of the system design based on numerical simulations and go on to suggest further steps for improvement. To the best of our knowledge, this is the first demonstration of a tunable CPA system beyond 1.1 μm. Considering the specific wavelength range, this wavelength-tunable CPA system is highly desirable for biomedical imaging, sensing, and parametric amplifiers.